Positive Teaching as an Instructional Innovation: Effects on Students’ Cognitive Learning Outcomes and Motivation in Biology Learning within Higher Education - Nosi Qadariah; Darti Busni; Agung Iranda (Bioeducation Journal, 2026)
This study investigates the effectiveness of positive teaching as an instructional innovation in enhancing students’ cognitive learning outcomes and learning motivation in biology courses, particularly on reproductive system topics. Preliminary observations indicated low levels of cognitive achievement and learning motivation, primarily attributed to the continued use of conventional, teacher-centered instructional methods. To address this issue, the Positive Teaching approach emphasizing appreciation-based instruction, emotional support, and interactive learning environments was implemented in the experimental group, while the control group continued with conventional teaching methods. The study employed a non-randomized pretest–posttest control group design to examine differences in cognitive outcomes and learning motivation between the two groups. The results demonstrated that the implementation of Positive Teaching significantly improved both students’ cognitive learning outcomes and learning motivation. These improvements were associated with the creation of a supportive classroom climate, increased student self-confidence, and enhanced ability to relate biological concepts to real-life contexts. This study provides valuable insights into the development of more adaptive and holistic instructional strategies aligned with the Merdeka Curriculum framework and contributes to the growing body of literature on the positive impacts of Positive Teaching beyond psychology-based learning contexts.